Nilai-Nilai Kristiani Dalam Karakter Siswa Kelas VIII di SMP Negeri 2 Tanah Siang Kabupaten Murung Raya - Karmila, Karmila; Tumbol, Stynie Nova; Rahmelia, Silvia (Danum Pambelum: Jurnal Teologi dan Musik Gereja, 2025)
Abstract Christian Education must be learned to students on the basis by Word of God and should be pursued jointly by teachers and parents, in order to create the expected Christian disposition or character of students. However, the facts show that the character of Christian teenagers is not yet in line between the material learned at school through Christian Education learning, and what is applied in daily life and in the community. Likewise, students at SMPN 2 Tanah Siang, Murung Raya still do not consistently apply Christian values in their daily lives. Based on the background of the problem above, the researcher is interested in identifying and describing Christian values in the character of students at SMP Negeri 2 Tanah Siang, Murung Raya, with the aim of 1) being able to identify and describe the Christian values that students learn in Christian Religious Education Subjects; 2) can identify and describe Christian values in students' characters. The data sources are class VIII students at SMPN 2 Tanah Siang, Murung Raya, teachers and students' parents. This research use qualitative approach using observation, interview and documentation study. The research results refer to the finding that there are still inconsistencies in the Christian character applied by students at school and outside school. Students generally have gained an understanding of the character of Christian values regarding “the fruits of the holy spirit” through Christian Education. In terms of application, students are still weak in the character of self-control. This is also caused by exposure to modern lifestyles and lack of parental control when children are at home. Keywords: Character, Christian, Education, Student Abstrak Pendidikan Agama Kristen (PAK) harus dibelajarkan kepada siswa dengan landasan Firman Tuhan yang mutlak dan sudah semestinya diupayakan bersama oleh guru dan orang tua, agar tercipta watak atau karakter Kristiani siswa yang diharapkan. Namun demikian fakta di lapangan memperlihatkan karakter remaja Kristen yang belum sejalan antara materi yang dipelajari di sekolah melalui pembelajaran PAK, dengan apa yang diterapkan dalam kehidupan sehari-hari di rumah dan di masyarakat. Demikian halnya siswa SMPN 2 Tanah Siang Kabupaten Murung Raya yang masih belum konsisten menerapkan nilai-nilai kristiani dalam kehidupannya sehari-hari. Berdasarkan latar belakang masalah di atas, peneliti tertarik untuk mengidentifikasi dan mendeskripsikan tentang nilai-nilai Kristiani dalam karakter siswa di SMP Negeri 2 Tanah Siang Kecamatan Tanah Siang Kabupaten Murung Raya, dengan tujuan 1) dapat mengidentifikasi dan mendeskripsikan nilai-nilai Kristiani yang dipelajari siswa dalam pembelajaran Pendidikan Agama Kristen; 2) dapat mengidentifikasi dan mendeskripsikan nilai-nilai kristiani dalam karakter siswa. Sumber data adalah siswa kelas VIII SMPN 2 Tanah Siang Kabupaten Murung Raya, guru PAK dan perwakilan orang tua siswa. Penelitian ini menggunakan pendekatan pendekatan kualitatif dengan teknik pengumpulan data observasi, wawancara dan studi dokumentasi. Hasil penelitian merujuk pada temuan bahwa masih adanya ketidakkonsistenan karakter Kristiani yang diterapkan siswa di sekolah dan di luar sekolah. Siswa secara umum telah mendapatkan pemahaman karakter nilai-nilai Kristiani tentang buah-buah roh melalui pembelajaran Pendidikan Agama Kristen. Dari segi penerapan siswa masih lemah dalam karakter penguasaan diri. Hal ini salah satunya juga disebabkan oleh terpaan gaya hidup modern dan kurangnya kendali orang tua saat anak di rumah. Kata kunci: Buah Roh, Karakter, Kristiani, Pendidikan Agama Kristen, Siswa